2012
DOI: 10.1016/j.ypmed.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Parent-focused change to prevent obesity in preschoolers: Results from the KAN-DO study

Abstract: Objective Present the immediate post-intervention results of Kids and Adults Now - Defeat Obesity!, a randomized controlled trial to enhance healthy lifestyle behaviors in mother-preschooler (2–5 years old) dyads in North Carolina (2007–2011). The outcomes include change from baseline in the child’s diet, physical activity and weight, and in the mother’s parenting behaviors, diet, physical activity, and weight. Method The intervention targeted parenting through maternal emotion regulation, home environment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
122
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(128 citation statements)
references
References 50 publications
5
122
1
Order By: Relevance
“…Notably, one interventional study aimed at preventing early childhood obesity observed reductions in instrumental and emotional feeding practices. 36 Parents of normal weight children describing an internal reaction to their personal experiences as their motivation for behavioral change is a novel finding. However, this observational finding is essentially what the emerging literature on using motivational interviewing describes.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, one interventional study aimed at preventing early childhood obesity observed reductions in instrumental and emotional feeding practices. 36 Parents of normal weight children describing an internal reaction to their personal experiences as their motivation for behavioral change is a novel finding. However, this observational finding is essentially what the emerging literature on using motivational interviewing describes.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Despite promising results in the treatment of adult obesity, 18 MI as a counseling tool for the prevention or treatment of childhood obesity has shown only a weak or no effect in children and their parents. [19][20][21][22][23][24] Too brief an intervention or follow-up period, and possibly limited intervention fidelity, have been proposed as explanations for the lack of an intervention effect. There is, however, an exception in 1 recent study, which presents a modest effect of MI compared with care as usual, when targeting overweight and obese preschool children and their parents.…”
mentioning
confidence: 99%
“…Based on the inform a tion avail able, 10 studies were considered to have low risk of bias (Chen et al , 2010(Chen et al , , 2011Gow et al , 2010;Kennedy et al , 2009;Kim et al , 2010;LaChausse, 2012;Luszczynska and Haynes, 2009;Østbye et al , 2012;Rosenkranz et al , 2010;Zask et al , 2012), nine had moder ate risk (Bayer et al , 2009;De Bock et al , 2012;Gentile et al , 2009;Gephart and Loman, 2013;Haire-Joshu et al , 2008;Hoffman et al , 2011;NeumarkSztainer et al , 2009;Siegel et al , 2010;van Wier et al , 2009), and six had high risk (Branscum et al , 2013;Foster et al , 2008;French et al , 2010;Spiegel and Foulk, 2006;Taylor et al , 2007;Warren et al , 2003). Nine studies repor ted random iz a tion by a computer, random number tables, or permuted blocks.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Nineteen of 25 studies repor ted posit ive effects on increas ing fruit and/or veget able consump tion (Bayer et al , 2009;Branscum et al , 2013;Chen et al , 2010Chen et al , , 2011De Bock et al , 2012;French et al , 2010;Gentile et al , 2009;Gephart and Loman, 2013;Haire-Joshu et al , 2008;Hoffman et al , 2011;Kennedy et al , 2009;Kim et al , 2010;LaChausse, 2012;Luszczynska and Haynes, 2009;Østbye et al , 2012;Spiegel and Foulk, 2006;Taylor et al , 2007;Warren et al , 2003;Zask et al , 2012), while five revealed no FV effects (Gow et al , 2010;Neumark-Sztainer et al , 2009;Rosenkranz et al , 2010;Siegel et al , 2010;van Wier et al , 2009). One study detected decreased FV consump tion (Foster et al , 2008).…”
Section: Effects On Fv Consump Tionmentioning
confidence: 99%
See 1 more Smart Citation